2021
DOI: 10.1039/d0cp05533f
|View full text |Cite
|
Sign up to set email alerts
|

Analysis of structural organization and interaction mechanisms of detonation nanodiamond particles in hydrosols

Abstract: Analysis of the structural organization of nanodiamond particles based on the interplay between Coulomb and van der Waals forces was performed.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
5
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 10 publications
(5 citation statements)
references
References 53 publications
0
5
0
Order By: Relevance
“…As mentioned above, there are many functional groups on the surface of DNDs and these functional groups can have a significant effect on the properties of DNDs. In recent studies the aggregation stability of DNDs hydrosols has been related to the interaction of charged particles in the functional groups on the surface [ 16 , 17 ]. Dispersion of DND aggregates using a range of modalities contributes to the formation of stable aqueous suspensions of DNDs.…”
Section: Fluorescence Imagingmentioning
confidence: 99%
“…As mentioned above, there are many functional groups on the surface of DNDs and these functional groups can have a significant effect on the properties of DNDs. In recent studies the aggregation stability of DNDs hydrosols has been related to the interaction of charged particles in the functional groups on the surface [ 16 , 17 ]. Dispersion of DND aggregates using a range of modalities contributes to the formation of stable aqueous suspensions of DNDs.…”
Section: Fluorescence Imagingmentioning
confidence: 99%
“…Such information is especially important in a biomedical context, since different particle shapes and aggregation may influence cell uptake and cell viability . Moreover, newer research has revealed the polydisperse and aggregated nature of DNDs in aqueous media, most likely due to their complex surface structures. ,, Unlike standard colloidal systems where particle assembly and (prevention of) aggregation can be controlled by surfactants, , theoretical calculations have shown that DNDs exhibit facet-dependent, unisotropical surface electrostatic potential distributions. These electrostatic potentials have been shown to promote ordered facet–facet connections resulting in chain and loop assemblies , which have been observed using transmission electron microscopy (TEM) (see Figure S1).…”
Section: Introductionmentioning
confidence: 99%
“…Cryo-TEM, unlike conventional TEM, holds the advantages of imaging the sample frozen in its native state, hence providing information about the dynamic formation process at high spatial resolution. It has been previously used for DND suspension characterization; ,, however, it has not been used to provide statistical analysis comparable with the bulk sample analysis like DLS and SAXS. Quantitative image analysis using ML allows us to process a large amount of image data and gain more statistics about the ensemble behavior of DNDs in solution.…”
Section: Introductionmentioning
confidence: 99%
“…It is extremely important to understand the nature of different DNDs behavior under an electric field for practical application. Although today there are studies on the mechanism of the positive electrorheological effect of hydrogenated DND particles [18,19], much less is known about the reasons for the electrophoresis of particles with a carboxylated surface. Since particles must be charged for electrophoresis, two hypotheses have been proposed in previous study to explain this phenomenon [20].…”
Section: Introductionmentioning
confidence: 99%